Literature and Its Learning in the Perspective of Curriculum Development History - Fatmah AR. Umar (TRANSBAHASA, 2021)
The present work aimed at exploring (1) the condition of Indonesian literature and its learning in the curriculum development perspective, (2) the past and the current learning orientation, (2) Indonesian literature learning in multiculturalism perspectives, and (3) efforts to accentuate a liberating, literary education and learning concept. In this qualitative descriptive research, all data were collected from documentation, observation, and interview. The results showed that: First, in the old order (Orde Lama), literature education was a separate subject before being integrated into the Indonesian language subject since the New Order (Orde Baru). Theoretical knowledge has long been emphasized in literature learning. To this day, literature education has focused on the creation and preservation of the culture of silence. Educators (teachers) have been plagued by being powerless and unable to express themselves. As a result, the teachers opt to remain silent, but they are trapped in a situation of being alienated from reality. Second, Indonesian literature learning, from the perspective of structuralism, indicates plurality embedded in the core of the Indonesian literary works that covers the aspects of culture, language, themes, and pronunciation. Third, efforts to accentuate a liberating, literary education and learning concept can be made through (i) writing, reading, and interpreting the literary works, the involvement of litterateurs in extracurricular activities (teaching and learning of literature), and (iii) taking advantages potential texts containing the socio-cultural concept of literature, and (iv) referring to the original principle of literature education.